Differences between student perceptions of the actual and the preferred science laboratory classroom learning environments at a South African college of education - Adams, William Edward (School of Education, 2016)
This preliminary research study aimed to investigate, with the aid of the Science Laboratory Environment Inventory (SLEI), the actual and the preferred laboratory environments as perceived by 264 first, second and third year college Science and Biology students in Cape Town, South Africa. This investigation sought to answer the following main questions: * Are the English and the Afrikaans versions of the SLEI valid and reliable for use as perceptive instruments in a South African context? * What are the relationships between variables such as class membership, the year level of study, the type or level of the science subject studied, the particular lecturer concerned, home language and gender and the students' perceptions of their science laboratory classroom environments? * Do appreciable differences occur between the actual and the preferred environments as perceived by the students? * Are the findings of the present investigation consistent with the results of parallel investigations undertaken overseas? The data was collected by means of standard answer sheets, and analysed by comparison of the mean scores, standard deviations, discriminant validities and the alpha reliabilities of the various scales of SLEI. Bibliography: p. 130-141.